A molecular dynamics investigation on effects of nanostructures on thermal conductance across a nanochannel. (October 2018) - Lin, T.; Li, J.; Quan, X.; Cheng, P.
Abstract: Molecular dynamics simulations are conducted to investigate effects of nanofins on thermal conductance of a nanochannel with two opposing walls at different temperatures. The nanochannel and nanofins are made of Pt with liquid Argon filled in between. It is found that the degree of thermal conductance enhancement across the nanochannel depends on combined effects of (i) confinement of liquid atoms in the nanogap between fins and (ii) lowering of coordinate number of fin atoms at the solid-liquid interface, both of which depend on the fin's width for a fixed pitch distance. It is also found that the thermal conductance across the nanochannel is increasing monotonously with fin's height, and that a notable temperature gap between confined liquid in the nanogap between fins and bulk liquid exists when the effect of fin-confinement is strong and the fin is sufficiently long. The existence of this temperature gap is because the enhanced interfacial thermal heat transfer at nanofin's sidewalls and the enlarged liquid conductive resistance between confined and bulk liquid. Due to the temperature gap between the confined liquid and the bulk liquid, the method chosen to compute the interfacial temperature difference can significantly influence the result of interfacial thermal resistance when nanofins are tall.